The U.S. Constitution for everyone - Gerberg, Mort.; United States (New York, NY Putnam Pub. Group, 1987)
Presents the text of the Constitution, explains its fundamentals, and traces events leading up to its adoption in 1788.
"A Perigee book."
Keywords: Constitutions -- United States; Constitutional law -- United States; Constitutions -- United States; Constitutional law -- United States